Impact Analysis of the NPEGEL A Study of Udalguri District of the State of Assam - Nuna, Anita (JOURNAL OF INDIAN EDUCATION, 2016)
This paper presents the contribution of initiatives undertaken under the National Programme for Education of Girls at the Elementary Level (NPEGEL) for the educational and overall development of tribal girls in two model cluster schools of Udalguri District of Assam. The analysis of initiatives focused on tracing out of the contribution of the NPEGEL programme in the educational improvement of tribal girls and also in raising their level of awareness and knowledge on three indicators concerning the issues of personal health and hygiene, self-esteem and self-confidence, and of girl child’s rights and some social issues associated with it. The efforts initiated in the field under the NPEGEL programme also revolved around these aspects. The empirical evidences reflected a significant contribution of two major action-oriented initiatives carried out by the implementing agency with the support of the NPEGEL fund i.e.: (i) development of ambience that promote gender-inclusive environment in the local community through community mobilization, and (ii) capacity-building programmes for girls in the educational and overall development of tribal girls. With regard to the aspects associated with the issue of overall development of tribal girls, it contributed significantly in raising their level of awareness on issues related to personal health and hygiene, self-esteem and self-confidence, and of girl child’s rights and some social issues associated with it. However, the study found that the targeted tribal girls were not using this awareness and knowledge into practice fully. With regard to the question of gender sensitivity among teachers, the study observed a misconceived notion of gender and issues associated with it in the minds of the targeted teachers in spite of being they exposed to the nuances of gender sensitivity in especially conducted sessions.